Complications with rotavirus: A single center experiences - Aldemir-Kocabaş, Bilge; Karbuz, Adem; Özdemir, Halil; Tural-Kara, Tuğçe; Tapısız, Anıl; Belet, Nurşen; Güriz, Haluk; Çiftçi, Ergin; İnce, Erdal (The Turkish Journal of Pediatrics, 2016)
Rotavirus is an important morbidity and mortality agent among previously healthy infants. Rotavirus gastroenteritis (RG) causes severe fluid and electrolyte imbalance and development of fatal complications during course of the disease, if untreated. Although there are few case reports in the literature regarding septicemia after RG, it is one of the most important complications of the disease. The main reason of septicemia is unknown but it can be associated with severe consequences such as septic shock, endocarditis, and even death. If complications are taken into consideration on the course of disease, morbidity and mortality can be reduced. Herein, we evaluated the clinical characteristics, incidence and types of the complications during RG in this retrospective study. We evaluated a total of 276 patients (164 male, 112 female) diagnosed with RG between January 2006 and February 2013 at the department of Pediatric Infectious Disease. Male to female ratio was 1.5 and the median age at admission was 12 months (1-102 months). None of the patients had a history of Rotavirus immunization. While overall complication rate was 44.2%, the most common complication related RG was electrolyte imbalance and the second common complication was septicemia (32.6% and 6.5%, respectively). Klebsiella, E. coli and Candida species were the most common isolated microorganisms from the blood cultures. Rotavirus gastroenteritis is still an important cause of morbidity in children which can cause serious complications such as sepsis. Lack of rotavirus vaccine in our national immunization program might contribute to the related complications and prolonged hospitalization, health care expenses and family work loss, as well.